(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
The objective of this study is in the theoretical discussion of the elements of visual language presented by Dondis (1997); Lupton and Phillips (2008); Gomes Filho (2009); Heller (2013); Bergström (2009); Leborg (2015) and other theorists who dialogue with them. The purpose is in the practical demonstration in the classroom of how such fundamentals are relevant in the creative process of graphic compositions. The research emphasizes the premise that the graphic designer, when mastering the visual language, understanding each of its constitutive elements, has better mastery, skill and creativity to develop graphic projects with good formal composition and high pregnancy of form. The methodology adopted was the bibliographic research and the case study. The results are the result of creative activities developed in the classroom with students from the graphic design course at UFG. From theoretical studies on the elements of composition and visual organization, dozens of graphic pieces were created by the students through the experimental method using different techniques and materials.